Value Co-Creation Behavior in Green Supply Chains: An Empirical Study - Xianliang Shi; Genzhu Li; Ciwei Dong; Yefei Yang (Energies, 2020)
As an important supply chain development strategy, green investment and sustainability are concerns of the government and enterprises. However, due to the high cost and low profit of green investment, a large number of small and medium-sized firms can be deterred from their implementation. Value co-creation has become a key measure to solve this problem. This article explores the relationship between the green supply chain (GSC) strategy, value co-creation, and corporate performance in the manufacturing environment, and considers the regulatory effects of internal environmental factors and external environmental pressures on this relationship. Based on data from 115 manufacturers in China, we tested the hypotheses, explained the statistical results, and identified key concerns for implementing GSC through value co-creation. The findings reveal that the GSC strategy can promote a high level of firms’ value co-creation with their supply chain partners, and different value co-creation modes have different effects on firm performance (i.e., operational performance, innovation performance, and financial performance). In addition, the findings indicate that macro-level external pressure and micro-level internal support could enhance such effects. This study enriches the literature with value co-creation modes and GSC management by integrating GSC strategies and value co-creation strategies, providing confidence to the firms and their supply chain partners in value co-creation, thus helping them to better implement a GSC strategy.